A Comment on Aumann's Bayesian View - Gul, Faruk (Econometrica, 1998)
In Aumann [1987], it is asserted that for those who adhere to the “...Bayesian view of the world, the notion of equilibrium is an un-avoidable consequence... ” I discuss two possible interpretations of the information model and show that neither interpretation supports this assertion. The hierarchy representation interpretation renders the prior stage meaningless and hence both the key assumption of Au-mann’s theory and its conclusion become impossible to interpret. The prior interpretation, on the other hand, is distinctively non-Bayesian. Furthermore, both the common prior assumption and the notion of having beliefs over one’s own actions are problematic in the latter interpretation. Key Words: correlated equilibrium, Bayesian view of probability, common prior assumption, Savage’s foundations of statistics. † I am indebted to Eddie Dekel-Tabak, David Kreps, and Robert Wilson for their help. Financial sup-port from the Alfred P. Sloan Foundation and the National Science Foundation is gratefully acknowledged. Aumann [1987] presents a result which he interprets as establishing that, for those who adhere to the “...Bayesian view of the world, the notion of equilibrium is an unavoidable consequence... ”1 The purpose of this comment is to refute this claim. An information model I = Ω, (Ti, pi)